PARK DESIGN FOR ELDERLY (CONTINUE AGE) IN WISMA LANSIA HUSNUL KHOTIMAH "AISYIAH" GUNUNG PATI SEMARANG - Dwi Ananta Devy; Upik Farida (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
The purpose of this study is 1) to describe the condition of the Khusnul Khotimah guesthouse in meetingspiritual / recreational and physical therapy needs for the elderly (2) to know the criteria for the elderlygarden in meeting the social and physical needs of the Wisma Khusnul Khotimah ‘Aisyiah’ (3) to designand design elderly garden design in Wisma Khusnul Khotimah ‘Aisyiah’ in meeting spiritual and physicalneeds.The approach of this research is qualitative with research subjects elderly residents. The informantof this research is the manager of the elderly guesthouse. The instruments of this study were observationguidelines, interview guidelines and documentation.The results of the study are (1) the condition of the Wisma Khusnul Khotimah ‘Aisyiah’ homestead parkhas provided facilities to fulfill spiritual / indoor needs and does not provide light physical / physicaltherapy activities (2) the needs of elderly residents are spiritual / outdoor facilities and the provision ofphysical facilities /Sports. The provision of these facilities needs to be equipped with ornaments that haveaesthetic value. (3) garden design for the elderly is to accommodate spiritual and physical needs. Keywords: Elderly Garden Design, Spiritual Needs, Physical Therapy Needs  ABSTRAKTujuan penelitian ini adalah 1) mendeskripsikan kondisi taman Wisma Khusnul Khotimah‘Aisyiah’dalam memenuhi kebutuhan rohani/rekreasi dan terapi fisik bagi lansia (2) mengetahui kriteriataman lansia dalam memenuhi kebutuhan sosial dan fisik di Wisma Khusnul Khotimah ‘Aisyiah’(3)membuat desain dan rancangan taman lansia di Wisma Khusnul Khotimah ‘Aisyiah’dalam memenuhikebutuhan rohani dan fisik. Pendekatan penelitian ini adalah kualitatif dengan subyek penelitian penghuniwisma lansia. Informan penelitian ini adalah pengelola Wisma Khusnul Khotimah ‘Aisyiah’. Instrumenpenelitian ini adalah pedoman observasi, pedoman wawancara dan dokumentasi. Hasil penelitian adalah(1) kondisi taman lansia Wisma Khusnul Khotimah ‘Aisyiah’telah menyediakan fasilitas untuk memenuhikebutuhan rohani/rekresi di dalam ruangan dan tidak menyediakan aktivitas ringan terapi fisik/olahraga(2) kebutuhan lansia penghuni adalah fasiltias rohani/rekreasi di luar ruangan serta penyediaan fasilitasfisik/olahraga. Penyediaan fasilitas tersebut perlu dilengkapi ornament yang mempunyai nilai estetika. (3)desain rancangan taman bagi lansia adalah mengkomodasi kebutuhan rohani dan fisik. Kata Kunci : Desain Taman Lansia, Kebutuhan Rohani, Kebutuhan Terapi Fisik